Chemometric analysis of Hymenoptera toxins and defensins: A model for predicting the biological activity of novel peptides from venoms and hemolymph - Saidemberg, Daniel M. [UNESP]; Baptista-Saidemberg, Nicoli B. [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier, 2011)
When searching for prospective novel peptides, it is difficult to determine the biological activity of a peptide based only on its sequence. The trial and error approach is generally laborious, expensive and time consuming due to the large number of different experimental setups required to cover a reasonable number of biological assays. To simulate a virtual model for Hymenoptera insects, 166 peptides were selected from the venoms and hemolymphs of wasps, bees and ants and applied to a mathematical model of multivariate analysis, with nine different chemometric components: GRAVY, aliphaticity index, number of disulfide bonds, total residues, net charge, pI value, Boman index, percentage of alpha helix, and flexibility prediction. Principal component analysis (PCA) with non-linear iterative projections by alternating least-squares (NIPALS) algorithm was performed, without including any information about the biological activity of the peptides. This analysis permitted the grouping of peptides in a way that strongly correlated to the biological function of the peptides. Six different groupings were observed, which seemed to correspond to the following groups: chemotactic peptides, mastoparans, tachykinins, kinins, antibiotic peptides, and a group of long peptides with one or two disulfide bonds and with biological activities that are not yet clearly defined. The partial overlap between the mastoparans group and the chemotactic peptides, tachykinins, kinins and antibiotic peptides in the PCA score plot may be used to explain the frequent reports in the literature about the multifunctionality of some of these peptides. The mathematical model used in the present investigation can be used to predict the biological activities of novel peptides in this system, and it may also be easily applied to other biological systems. © 2011 Elsevier Inc.
Keywords: Insect venoms; PCA; Polycationic peptides; System biology; Toxins; chemotactic peptide; defensin; Hymenoptera venom; kinin; mastoparan; peptide; tachykinin; venom; algorithm; alpha helix; ant; bee; biological activity; chemometric analysis; disulfide bond; electricity; hemolymph; Hymenoptera; principal component analysis; priority journal; wasp; Algorithms; Amino Acid Sequence; Animals; Anti-Infective Agents; Arthropod Venoms; Biological Agents; Defensins; Disulfides; Hemolymph; Hydrophobic and Hydrophilic Interactions; Isoelectric Point; Models, Theoretical; Peptides; Principal Component Analysis; Protein Structure, Secondary; Apoidea; Formicidae; Hexapoda